Weighted estimate for a class of matrices on the cone of monotone sequences - Taspaganbetova, Zhanar Abdugalievna (Eurasian Mathematical Journal, 2012)
Weighted estimate for a class of non-negative lower triangular matrices has been established on the cone of monotone sequences.